Asylum migration and implications for countries of origin - Khalid Koser; Nicholas Van Hear (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
The purpose of this paper is to synthesize what is known about the influence of asylum migration on countries of origin. It combines an analysis of data, a review of the literature and empirical examples from our own research. In the first section we consider the effects of the absence of refugees on countries of origin, focusing on the scale of movements, the characteristics of refugees, where they go and their length of time in exile. In the second section, we review the evidence about the influence of asylum-seekers and refugees on their country of origin from exile. Third, we consider the implications for countries of origin of the return of asylum-seekers and refugees. The conclusion acknowledges the limited state of current knowledge and draws out some policy implications.
Keywords: F22; O15; 330; forced migration; remittances; post-conflict reconstruction; development